Motivasi Mahasiswa dalam Melakukan Self-Disclosure di Instagram - Latifa, Dina Tiara (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the influence of social media integration, basic psychological need satisfaction, and risk–benefit perception on students’ motivation to engage in self-disclosure on Instagram. The participants consisted of 39 active university students aged 19–25, selected through purposive sampling based on their active Instagram usage and experience in sharing personal content on the platform. Data were collected via an online Likert-scale questionnaire using adapted instruments, including the Revised Self-Disclosure Scale, Social Media Use Integration Scale, Basic Psychological Need Satisfaction Scale, and a risk–benefit perception scale. Data analysis was conducted using descriptive statistics, Pearson correlations, and multiple linear regression. The findings reveal that students’ motivation for self-disclosure falls within a moderate category. Basic psychological need satisfaction emerged as the most significant predictor of self-disclosure motivation (β = 0.646; p < 0.001), whereas social media integration and risk–benefit perception did not show significant effects. The results highlight that internal factors—particularly the fulfillment of autonomy, competence, and relatedness—play a greater role in students’ online self-disclosure than cognitive considerations of risks and benefits. These findings provide valuable implications for digital literacy programs in higher education, emphasizing the importance of self-awareness, privacy management, and psychological well-being in online communication practices.